Switching Home Energy with IoT-Powered Solar - Hashim, Mohammad Hanan Yasir; Mohd Noh, Faridah Hanim (Progress in Engineering Application and Technology, 2022)
: Technology has improved and continues to evolve. Various technologies have been created to make daily human life easier while maintaining comfort and almost all technologies have been developed requiring electrical power. With the new norm following Covid-19, many Malaysians now spend a lot of time at home. If someone is ever about to install solar panels in a home, now is the best time to do so. One can save on electricity bills while potentially earning a side income. Therefore, the installation of a solar system for a home is highly recommended. This solar system should be developed using IoT developments that are so popular nowadays. The development of IoT (Internet of Things) technology today will help solve this problem, not only making it easier for users to organize their solar systems, but also allowing them to track electricity consumption for electrical goods. house. One of the systems based on IoT principles is the introduction of home automation systems. Home automation allows you to access your home control system from anywhere in the world from a mobile device. The project presents the design and implementation of the Arduino Uno with the ESP8266 Wi-Fi module, and 5V relay and is based on the IoT concept. The system can be connected to a home electrical system so that users can control and monitor their system using their internet devices anywhere and anytime through the platform Blynk. The system is also equipped with several sensors for control unit input that allow users to operate the switch in a variety of ways, either online or by manual switches.